Restrukturisasi Kredit Sektor Porperti dan Real Estate - muryati marzuki (Fakultas Hukum Universitas Islam Indonesia, 2002)
The discussion about restructurization for property credit and reaiestate is one of interesting issue to be discussed from the jurisdical view. Recently, the government have provided various kinds ofrestructurization for property credit andreaiestate which is the best step to solvenonperformance loan. However, the solution ofloanmust be put into in action by considering forthe persistence ofbusiness forpropertysector and real estate.The consequency of restructurization is enabled the changes of position and role for capital management and loan stmcture.